2016
DOI: 10.1159/000447259
|View full text |Cite
|
Sign up to set email alerts
|

Malignancies in Patients with Inflammatory Bowel Disease: A Single-Centre Experience

Abstract: Background: Gastrointestinal and extraintestinal malignancies are long-term complications in patients with inflammatory bowel disease (IBD), likely as a result of chronic inflammation and the use of immunosuppressive medications used to control inflammation. Here, we assessed the frequency of malignancies in a large tertiary IBD centre at the University Hospital Zurich. Methods: We performed a retrospective analysis of data from 1,026 patients from our IBD clinic treated between 2007 and 2014. Results: Twenty … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 32 publications
1
18
0
1
Order By: Relevance
“…More importantly, patients with CD and UC are at increased risk of both intestinal and extraintestinal malignancies, and they have a higher risk of developing invasive cancer than the general population, including lymphoma, melanoma, and cholangiocarcinoma ( 7 ). However, there is a lack of conclusive evidence demonstrating the risk of urinary bladder cancer (BC), the ninth most common cancer around the world, in IBD patients ( 8 , 9 ). Here, we carried out a comprehensive meta-analysis to investigate the relationship between IBD and the risk of BC.…”
Section: Introductionmentioning
confidence: 99%
“…More importantly, patients with CD and UC are at increased risk of both intestinal and extraintestinal malignancies, and they have a higher risk of developing invasive cancer than the general population, including lymphoma, melanoma, and cholangiocarcinoma ( 7 ). However, there is a lack of conclusive evidence demonstrating the risk of urinary bladder cancer (BC), the ninth most common cancer around the world, in IBD patients ( 8 , 9 ). Here, we carried out a comprehensive meta-analysis to investigate the relationship between IBD and the risk of BC.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it has been reported that patients who achieve mucosal healing have lower rates of hospitalization and a lower risk of colectomy [1, 2]. Furthermore, in UC patients, a prolonged disease course and immunosuppressive therapy increase the risk for emerging malignancies compared to those who have a normal colon [22-24]. …”
Section: Discussionmentioning
confidence: 99%
“…Oral 5-ASA treatment is also important for inhibiting extension of ulcerative proctitis [7]. Long-term cases of ulcerative colitis even in proctitis type may be in risks of cancer [12]. …”
Section: Epidemiologymentioning
confidence: 99%